Advances and recent trends in cobalt-based cocatalysts for solar-to-fuel conversion. (September 2021) - Soni, Vatika; Xia, Changlei; Cheng, Chin Kui; Nguyen, Van-Huy; Nguyen, Dang Le Tri; Bajpai, Archana; Kim, Soo Young; Le, Quyet Van; Khan, Aftab Aslam Parwaz; Singh, Pardeep; Raizada, Pankaj
Highlights: Various configurations of anchored cocatalysts were summarized. Alluring functions of cobalt family cocatalysts have been explored. Diverse fabrication strategies of cobalt cocatalysts have been discussed. The role of cobalt cocatalysts in enhanced photocatalytic reaction was explored. Finally, challenges and future perspectives were concluded. Abstract: Photocatalysis is considered to be one of the preeminent routes to realize sustainable O2 and H2 evolution, as well as CO2 reduction. Owing to various limitations, i.e. insufficient surface area, active sites, charge isolation, high overpotential, etc. associated with a single photoactive semiconductor, it is challenging to convert adsorbed H2 O and CO2 to CO, H2, CH4, CH3 OH, O2, etc. by harvesting solar light. Among popular cocatalysts, earth-abundant cocatalysts exhibited great potential in the area of photocatalysis and are highly significant in accelerating reaction kinetics happening on the surface of semiconductors. Recently, other than the costly noble metals cocatalysts, earth-abundant cobalt based materials can be used as efficient cocatalysts, which effectively amended the photoactivity of photoactive semiconductors by forming stable junctions. Herein, in this all-inclusive review, the recent progress in cobalt based materials as cocatalysts applied in photocatalytic CO2 conversion and water splitting are concisely summarized. Special emphasis is placed on the surface modification principle, design strategies, and loading techniques for further amending the redox potentials of cobalt based cocatalysts for energy applications. Particularly, five types of amendment stratagems based on enhanced solar energy harvesting accelerated charge tunneling, exposed active centers, strengthened photostability, and lowered overpotential have been extensively highlighted and summarized. Typically, the anchoring of both reductive and oxidative (dual) cocatalysts have been explored, which depicted the synergistic behaviour of dual cocatalysts in amending surface properties for improving the photocatalytic CO2 reduction, H2 and O2 generation. Finally, this review addresses the emerging current perspectives as an insight into future research directions in this field to develop more efficient cocatalysts which effectively helped in the mitigation of energy and environmental issues. Graphical Abstract: The present review emphasized the important roles of cobalt based cocatalysts in improving the solar-to-chemical conversion efficiency for photocatalytic solar fuel production. We aim to outline the recent progress on the surface and interface design, followed by the fabrication strategies and loading methods of cobalt based cocatalysts for water splitting and CO2 reduction reactions. Image, graphical abstract